2009
DOI: 10.1681/asn.2008040377
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Role of Donor Dendritic Cells in Rejection versus Tolerance of Allografts

Abstract: Little is known about heart tissue/donor dendritic cells, which play a key role in mounting alloimmune responses. In this report, we focus on three primary features of donor dendritic cells: their generation, their trafficking after transplantation, and their role in regulating tolerance versus rejection. Using transgenic mice as donors of heart allografts enabled us to monitor trafficking of donor dendritic cells after transplantation. Donor dendritic cells rapidly migrated into secondary lymphoid tissues wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Moreover, donor APCs lacking PDL1 also affected the outcome of CTLA4-Ig treated animals preventing complete tolerance in most but not all recipients, suggesting a contributory role. This latter finding expands a prior observation that donor dendritic cells are important for tolerance development (15) and suggests that PDL1 on donor APCs might be involved in this process.…”
Section: Pdl1 Of Donor Endothelium In Allograft Tolerance Similar Sursupporting
confidence: 87%
“…Moreover, donor APCs lacking PDL1 also affected the outcome of CTLA4-Ig treated animals preventing complete tolerance in most but not all recipients, suggesting a contributory role. This latter finding expands a prior observation that donor dendritic cells are important for tolerance development (15) and suggests that PDL1 on donor APCs might be involved in this process.…”
Section: Pdl1 Of Donor Endothelium In Allograft Tolerance Similar Sursupporting
confidence: 87%
“…1D). The frequency of IFN-g-producing cells was also assessed as an index of alloreactivity, as has been described previously (25,37). IFN-g production following coculture of allogeneic T cells and isc DCs was significantly upregulated by ELISPOT in a dose-dependent manner (n = 3 experiments; p = 0.026; Fig.…”
Section: Results Isc Dcs Exhibit Increased Allostimulatory Activitymentioning
confidence: 85%
“…As the most potent APCs, DCs have the capability to determine the early fate of allografts following transplantation and potentially following ischemia. We have shown that donor DCs from cardiac allografts migrate to recipient lymphoid tissue as early as 3 h posttransplant (25), and it is well established that efficient DC migration results in T cell priming and proinflammatory cytokine production (13,27,30). Our goal was therefore to examine the specific effect of isc insult on DCs, whereby a finding of augmented allostimulatory function of DCs would implicate DCs in having a primary role in ischemiainduced allograft immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 In the case of cardiac transplants, the aforementioned DST+ anti-CD40L is effective in inducing allotolerance in wild-type mice, but not in CXC3R1 "null" mice naturally deficient in tissue-resident DC and macrophages. 53 Depletion of heart-resident tissue macrophages by peritransplant antibody treatment led to accelerated cardiac allograft vasculopathy in rats, 54 a phenomenon also seen in combined cardiac-bone marrow, but not in combined cardiac-liver transplantation, where vascular architecture and tissue resident macrophages were preserved long after transplant surgery. 55 Sustaining "tissue-appropriate" immunity immediately after transplantation is likely critical for long-term tolerance with excellent graft function.…”
Section: Resultsmentioning
confidence: 99%